Quantitative Characterization of Shale Micro-fracture in the Yuanba Area of the Sichuan Basin by Micro X-ray Tomography - LI Lei; HAO Jing-yu; XIAO Ji-lin; LI Ping-ping; ZHANG Zheng-chen; ZOU Hua-yao (Yankuang ceshi, 2020)
BACKGROUND Quantitative study of micro-fracture in shale is conducive to understanding reservoir type and evaluating the shale gas exploration potential. Micrometer X-ray tomography (micro-CT) is currently the most direct way to observe and measure micro-fracture. OBJECTIVES To qualitatively and quantitatively characterize the micro-fracture in the shale of the Da'anzhai Member of the Yuanba area of the Sichuan Basin, and to evaluate the exploration potential of shale gas. METHODS Micro-CT technology was used, through the identification and statistics of micro-fracture on the micrometer CT two-dimensional image. The micro-fracture porosity of shale samples was calculated quantitatively. Combined with the total porosity of shale samples obtained by porosimetry, the proportion of micro-fracture in the total pore space of shale was quantitatively evaluated. RESULTS The micro-fracture in shale were mainly structural micro-fracture with the width of 0-12μm. They were layered in three-dimensional space. The total porosity of shale was 2.24%-4.60% (average 3.48%), in which the micro-fracture porosity was 0.25%-1.06% (average 0.82%), accounting for an average of 23.28% in the total pore space. The development degree of micro-fracture was similar to that of the marine Longmaxi Shale in the Jiaoshiba area of the Sichuan Basin with the average micro-fracture porosity of 0.3%-1.3% that accounted for 6.1%-22.4% of the total porosity. The shale in the Da'anzhai Member of the Yuanba area was a pore-type reservoir with abundant nano-scale matrix pores, which was conducive to the enrichment of shale gas. Meanwhile, the development of micro-fracture can communicate with many isolated matrix pores, which was conducive to high shale gas production. CONCLUSIONS The shale in the Da'anzhai Member of the Yuanba area is a pore-type reservoir with widespread micro-fracture, indicating that the area has high and stable shale gas pore conditions and good exploration potential.